Effects of Dendrobium Polysaccharides on the Functions of Human Skin Fibroblasts and Expression of Matrix Metalloproteinase-2 under High-Glucose Conditions - Yajia Li; Ziqin Cao; Qiangxiang Li; Chenxu Wang; Zhuo Zhou (International Journal of Endocrinology)
The effects of Dendrobium polysaccharides (PDC) on the functions of human skin fibroblasts (HSFs) and expression of matrix metalloproteinase-2 under high-glucose conditions and exploration of the underlying mechanism remain unclear. We used the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) analysis and flow cytometry to evaluate the cell viability and apoptosis. The collagen levels were determined by the Sircol™ Collagen Assay. Real-time quantitative polymerase chain reaction (RT-PCR) was used to detect the expression of matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase inhibitor (TIMP-2) mRNA. We found the following: (1) under the high-glucose condition, the HSF cell viability, the expression of TIMP-2 mRNA, and the collagen levels were reduced, while the apoptosis rate and the expression of MMP-2 mRNA increased (P<0.05). (2) In the high-glucose + PDC group, the PDC reversed the changes in the collagen level, viability, and apoptosis rate of the HSF cells caused by high glucose, with the expression of protein and TIMP-2 mRNA increased and the level of MMP-2 mRNA decreased (P<0.05). This is the first time attempting to reveal that PDC can exhibit protective effects on HSF under high-glucose conditions, which may be related to the upregulation of the TIMP-2 expression and inhibition of the MMP-2 expression.